Photoelectrochemical Degradation of Contaminants of Emerging Concern with Special Attention on the Removal of Acetaminophen in Water-Based Solutions - Sacco, Nicolás Alejandro (2023)
Despite being an indispensable medium for life and the environment, the deterioration of water quality continues to be a matter of great concern for the scientific community since this problem has generated the need to develop processes for water treatment. Among the wide variety of types of contaminants, the presence of contaminants of emerging concern (CECs) has become an issue of global concern, since they are present in water in low concentrations and can persist in the environment, bioaccumulate and be toxic to human health and aquatic biota. Among CECs, this review focuses on pharmaceutical removal; what favorable effects they have on human and animal health are widely recognized, but the consequences or risks associated with the constant disposal of these products to the environment, through the manufacturing process, consumption, biological excretion or inappropriate disposal, are an area under constant study. The presence of pharmaceuticals in water represents a high risk to the environment because they contain active ingredients that were designed to induce specific pharmacological effects but, when dissolved in water, reach non-target populations and cause undesirable toxicological effects. This review pays attention to the photoelectrochemical removal of paracetamol (PTM), as a model molecule, from water, employing different photoactive materials (TiO2, BiVO4, ZnO and tungsten oxides) and the main parameters affecting their performance. The main goal of the present review is to facilitate future researchers to design their experiments concerning the PEC processes for the degradation of pharmaceuticals, specially PTM, and the existing limitations of each system.